Location technologies in international context - Wilken, Rowan; Goggin, Gerard 1964-; Horst, Heather A. (Internationalizing media studies, 2019)
Location Technologies in International Context offers the first international account of location technologies (in an expanded sense) and brings together a range of contributions on these technologies and their various cultures of use within the Global South. This collection asks: How, within the Global South, do location technologies differ across national markets, geo-linguistic communities and cultural contexts? What are the contrasting or shared meanings and practices associated with location technologies? And what innovative practices and new (or reinvigorated) theory may emerge from attention to the Global South? In exploring these questions, the collection contributes to our understanding of social, cultural, gendered and political relations on a global and local scale. Location Technologies in International Context is ideal for a range of disciplines, including cultural, communication and media studies; anthropology, sociology and geography; new media, Internet and mobile studies; and informatics and development studies